Modelling Capercaillie (Tetrao urogallus) lek sites distribution and their limiting factors in a central Norwegian managed forest landscape - Thingstad, Per Gustav; Daverdin, Marc; Speed, James D. M. (Ornis Norvegica, 2018)
Forest management has substantially altered Fennoscandian forests through clear-cutting practices started during the 1950s. Impacts on the natural biodiversity in mature boreal forest have been inevitable. The Capercaillie (Tetrao urogallus) is often regarded as an indicator species for natural old growth forest, displaying on traditional lek sites during spring. In a heterogeneous forest landscape of two adjoining municipalities in central Norway we studied whether forest management or other environmental factors can have influenced the lek distribution. We identified 15 active leks and 12 recently abandoned leks. The maximum entropy distribution modelling (MaxEnt) was used to investigate factors associated with lek distribution at two different scales, where the scale reflecting the lek site areas gave the most adequate result. Active leks were predominantly associated with mature stands of forest. In 65% of the study area the habitat suitability for lekking was most influenced by forest management. Furthermore, the recently abandoned leks were found less frequently in low productive and mature forests than the still active ones, implying that previous leks in productive forest stands may have been lost through logging. Based on our data we have developed models for the predicted distribution and the current limiting factors, showing that altered forest management could improve lek site suitability in large parts of this boreal forest.